Characterization of Type I and Type II nNOS-Expressing Interneurons in the Barrel Cortex of Mouse - Perrenoud, Quentin; Geoffroy, Hélène; Gautier, Benjamin; Rancillac, Armelle; Alfonsi, Fabienne; Kessaris, Nicoletta; Rossier, Jean; Vitalis, Tania; Gallopin, Thierry (Frontiers in Neural Circuits, 2012)
In the neocortex, neuronal Nitric Oxide-Synthase (nNOS) is essentially expressed in two sets of GABAergic neurons: type I neurons displaying a high expression and type II neurons displaying a weaker expression. Using immunocytochemistry on mice expressing GFP under the control of the glutamic acid decarboxylase 67k (GAD67) promoter we studied the distribution of type I and type II neurons in the barrel cortex and their expression of parvalbumin (PV), somatostatin (SOM) and vasoactive intestinal peptide (VIP). We found that type I neurons accumulated in deeper layers and expressed SOM (91.5%) while type II neurons concentrated in layer II/III and VI and expressed PV (17.7%), SOM (18.7%) and VIP (10.2%). We then characterised 42 nNOS transcribing neurons ex vivo, using whole-cell recordings coupled to singe-cell RT-PCR and biocytin labelling. Unsupervised cluster analysis of this sample disclosed four classes. One cluster (n=7) corresponded to large, deep layer neurons, displaying a high expression of SOM (85.7%) and were thus very likely to correspond to type I neurons. The three other clusters were neurogliaform-like interneurons (n=19), deep layer neurons transcribing PV or SOM (n=9) and neurons transcribing VIP (n=7), matching the features of type II cells. Finally, we performed nNOS immunohistochemistry on two mouse lines in which GFP/YFP labelling revealed the expression of two specific developmental genes (Lhx6 and 5-HT3A). We found that type I neurons expressed Lhx6 but never 5-HT3A, indicating that they originate in the medial ganglionic eminence (MGE). Type II neurons expressed Lhx6 (63%) and 5-HT3A (34.4%) supporting that they derive either from the MGE or from the caudal ganglionic eminence (CGE) and the entopeduncular preoptic area (AEP/PO). Together, our results support the view that type I neurons form a particular class of SOM-expressing neurons while type II neurons are heterogeneous and comprise at least three classes.